Prevalence of Cluster Headache in a Population-Based Sample in Germany - Katsarava, Z; Obermann, M; Yoon, M-S; Dommes, P; Kuznetsova, J; Weimar, C; Diener, HC (Cephalalgia, 2007)
A population-based sample of 6000 inhabitants of the city of Essen in Germany was screened using a standard questionnaire for possible cluster headache (CH). Fifty-six percent responded (N = 3336, 50.5% of them women, mean age 44.7 ± 12.7 years). All suspected cases (N = 182) were interviewed by a neurologist. Four subjects with CH (three men) were identified. The 1-year prevalence of CH was estimated to be 119/100 000 (95% confidence interval 3, 238/100 000).